2020
DOI: 10.1001/jamaoto.2019.4161
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Image Guidance in Endoscopic Sinus Surgery

Abstract: IMPORTANCE More than a quarter-million cases of endoscopic sinus surgery (ESS) are performed annually in the United States. Most surgeons use image-guided systems as an adjunct during surgery in certain situations. Understanding the association of image-guided surgery (IGS) with surgical outcomes, complications, and surgeon factors is paramount.OBSERVATIONS Three systematic or evidenced-based review articles demonstrated no clear evidence that IGS improves surgical outcomes for chronic rhinosinusitis, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…In a subsequent meta‐analysis, Vreugenberg et al, who focused on complex cases only, confirmed that IGS is associated with fewer total, major and orbital complications, but not minor complications and severe hemorrhage 2101 . Both of these reports have been criticized because they cannot address the bias intrinsic to the underlying publications that they summarize and review 2102 …”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 99%
“…In a subsequent meta‐analysis, Vreugenberg et al, who focused on complex cases only, confirmed that IGS is associated with fewer total, major and orbital complications, but not minor complications and severe hemorrhage 2101 . Both of these reports have been criticized because they cannot address the bias intrinsic to the underlying publications that they summarize and review 2102 …”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 99%
“…Navigation based surgery is a useful tool for the surgeon and has been widely used in sinus surgery [ 41 , 42 ]. The American Academy of Otolaryngology – Head & Neck Surgery has published a position statement regarding the appropriate indications for computer-guided sinus surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The American Academy of Otolaryngology – Head & Neck Surgery has published a position statement regarding the appropriate indications for computer-guided sinus surgery. These indications include: (1) revision surgery; (2) distorted anatomy (developmental, traumatic or postoperative); (3) extensive sino-nasal polyposis; (4) pathology of the frontal, posterior ethmoid and sphenoid sinuses; (5) disease involving the skull base, orbit, optic nerve or carotid artery; (6) CSF rhinorrhea or other skull base defects and (7) benign or malignant sino-nasal neoplasms [ 41 ]. A surgeon’s choice to use 3D image guided surgery technology may rely on these official indications as well as his preference and comfort.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of robust scientific evidence to determine indications and recommend the use of IGS in CRS. Improvements in surgical efficacy and safety are believed to be relevant 21. This review seeks to analyse trials that compare ESS with and without IGS.…”
Section: Introductionmentioning
confidence: 99%